Foreign MBA: Potential Managers for American International Corporations - Alpander, Guvenc G. (Journal of International Business Studies, 1973)
The foreign MBAs comprise an almost untapped recruitment source of international personnel. Only a few of the foreign MBAs receive employment offers although many of them are willing to be employed in the U.S. international firms.